Micro Nozzle Assisted Spraying Process for Re‐crystallization of Submicrometer Hexanitrostilbene Explosive. Issue 7 (4th July 2018) - Gupta, Shallu; Kumar, Pal Dinesh; Jindal, Deepika; Sharma, Sandeep; Agarwal, Arun; Lata, Prem
Abstract: Hexanitrostilbene has excellent thermal and shock stability, and shelf life. It has reliable initiation functioning when subjected to short duration pressure pulse stimuli. These characteristics make it one of the potential explosives for miniature devices such as exploding foil initiators, through bulkhead initiator, and fuzes for high 'g' applications. It also finds wide application in devices used for civilian applications such as mining and oil exploration. However, preparation of submicrometer HNS (sm‐HNS) explosives and batch‐to‐batch variation is a challenging task in terms of filtering, repeatability of particle size and shape distribution. In our research work, micro nozzle assisted spraying process (MNASP) was developed. The MNASP setup consists of micro fuel nozzle, pressure cylinder for HNS solution, flow meter and pressure gauges. The process attributes such as stirring rate, pressure, temperature, nozzle diameter, flow rate, ultra‐sonication frequency were optimized using weighted average method of Analytical Network Process (ANP) techniques. Laser diffraction‐based particle size analysis showed that sm‐HNS in the range of 300 to 700 nm, with average particle size of 515 nm and narrow standard deviation of 34 nm can be obtained using this process with very high consistency in batch‐to‐batch preparation. 1 H NMR investigations were carried out to confirm the purity of sm‐HNS. FTIR spectra confirmed the structure of sm‐HNS. The process is a unique laboratory scale table‐top pilot plant which is highly repeatabe under same conditions, and cost‐effective for large scale production at the rate of 50 grams per hour. The advantage of consistency in preparation of sm‐HNS with narrow particle size distribution is observed in performance of exploding foil initiators. There is consistency in threshold firing voltage of 1.5 kV, with standard deviation of 147 V. Abstract :